Interactive story graph structure for digital storytelling / Nur Azima Alya Narawi …[et al.] - Alya Narawi, Nur Azima; Abd Rahman, Hayati; Mohamed Shaari, Nazrul Azha; Wan Hussin, Wan Ya (Universiti Teknologi MARA, 2020)
The flow of a storyline should be structured well and organized to make it understandable and complete. The most enticing and fascinating storytelling nowadays is digital storytelling, as all the information and entertainment move into digital devices. To make digital storytelling more interactive and attractive, some interactive features, such as interactivity, iteration, and multioption incorporated in the story structure. Nevertheless, the interactive features should be explained well in the story structure to ease the process of interpreting the interactive storyline. However, the existing story structure could not support those features. Therefore, the creation of a new story structure will help the process of interpreting an interactive storyline with those interactive features. In this paper, a new story structure known as Interactive Story Graph Structure (ISGS) that blends well with the interactive features by modifying the existing story structure approach is proposed. The flow of a storyline using the proposed story structure can be created by applying a few new symbols that match the storyline by following the guidelines of making a new story structure. The new story structure has been evaluated by ten experts that have looked at the acceptance and usability of the new story structure as part of the process to interpret the interactive storyline for digital storytelling. The results of the evaluation had achieved a value of 88.89% by analyzing the data from descriptive analysis and bar charts. This study suggests the ISGS add more interactive features to produce interactive digital storytelling with the various flow of story structures embedded with more features provided.